2014
DOI: 10.1371/journal.pone.0107722
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Epigenetic Changes in Chromosomally Stable and Unstable Progeny of Irradiated Cells

Abstract: Radiation induced genomic instability is a well-studied phenomenon, the underlying mechanisms of which are poorly understood. Persistent oxidative stress, mitochondrial dysfunction, elevated cytokine levels and epigenetic changes are among the mechanisms invoked in the perpetuation of the phenotype. To determine whether epigenetic aberrations affect genomic instability we measured DNA methylation, mRNA and microRNA (miR) levels in well characterized chromosomally stable and unstable clonally expanded single ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 45 publications
2
10
0
Order By: Relevance
“…They found differential expression of ALDH1A3/ RA inducible genes that promote or suppress tumor growth in dependency of the DNA methylation state. This supports the role of epigenetic regulatory mechanisms in the radioresponse of cells [ 37 ]. Also for Non-small-cell lung carcinoma (NSCLC) ALDH1A3 was described as pre-dominant ALDH isoform, which on one hand associated with well differentiated lung cancer with good prognosis but on the other hand drives the tumorigenic and clonogenic potential of NSCLC cells [ 38 ].…”
Section: Discussionsupporting
confidence: 82%
“…They found differential expression of ALDH1A3/ RA inducible genes that promote or suppress tumor growth in dependency of the DNA methylation state. This supports the role of epigenetic regulatory mechanisms in the radioresponse of cells [ 37 ]. Also for Non-small-cell lung carcinoma (NSCLC) ALDH1A3 was described as pre-dominant ALDH isoform, which on one hand associated with well differentiated lung cancer with good prognosis but on the other hand drives the tumorigenic and clonogenic potential of NSCLC cells [ 38 ].…”
Section: Discussionsupporting
confidence: 82%
“…Indeed, similar to our demonstration here of LINE‐1 remethylation levels exceeding the original levels, some of the early work on 5‐azacytidine (5‐azaC) induced DNA demethylation also demonstrated a reacquisition of methylation levels that surpassed the original levels upon withdrawal of 5‐azaC [Bender et al, ]. Although arsenic was the focus of the work reported here, there is also evidence that other environmental exposures, for example ionizing radiation, can similarly perturb genome stability, imposing so‐called bystander effects characterized by a growing awareness of altered global genome methylation and LINE‐1 sequence methylation coordinated with evidence of delayed effects and persistence of epigenome modulation [Goetz et al, ; Baulch et al, ; Luzhna et al, ].…”
Section: Discussionsupporting
confidence: 82%
“…With a growing interest in radiation epigenetics, a number of studies have shown that radiation-induced changes in DNA methylation are not unidirectional; LINE-1 DNA hypo- and hypermethylation can be observed, as well as an absence of changes in DNA methylation, especially at doses below 1 Gy (3337). Those differences could be explained by the different types of radiation and doses, models used, as well as different methods of DNA methylation analysis.…”
Section: Repetitive Elements As a Tool To Study Radiation Epigeneticsmentioning
confidence: 99%